2017
DOI: 10.1590/1980-57642016dn11-020007
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of depression in patients with mild cognitive impairment in Parkinson's disease

Abstract: ObjectiveTo investigate the most frequent depressive symptoms and their association with cognition in Parkinson's disease (PD) patients with mild cognitive impairment (MCI).Methods48 patients with PD and 44 controls (CG), aged between 50 and 80 years and with at least 4 years of formal education, all with MCI and none diagnosed with depression, were assessed. Patients and controls were matched for age, education, and Mini-Mental State Examination (MMSE) score. Participants underwent clinical evaluation with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
4
0
2
Order By: Relevance
“…Since our PD patients reported a wide range in disease duration (from 1 to 14 years), and considering the known impact of age and disease duration on cognitive, mood and behavioral symptoms [33][34], all the correlation analyses were controlled for age and disease duration. Although there is evidence that depression is associated with cognitive impairment in PD [56], our (study) PD patients reported similar BDI scores compared to controls. For this reason, it is unlikely that the observed cognitive deficits are due to their affective state.…”
Section: Discussionsupporting
confidence: 40%
“…Since our PD patients reported a wide range in disease duration (from 1 to 14 years), and considering the known impact of age and disease duration on cognitive, mood and behavioral symptoms [33][34], all the correlation analyses were controlled for age and disease duration. Although there is evidence that depression is associated with cognitive impairment in PD [56], our (study) PD patients reported similar BDI scores compared to controls. For this reason, it is unlikely that the observed cognitive deficits are due to their affective state.…”
Section: Discussionsupporting
confidence: 40%
“…Episodic memory impairment in Parkinson's disease (PD) is linked to a decrease in functional ability (Cholerton et al., 2020), reduction in quality of life (Vasconcellos et al., 2019), and an increase in other neuropsychiatric symptoms (Dissanayaka et al., 2017; Malak et al., 2017). It has also been linked to more rapid disease progression (Tsiouris et al., 2020), which raises fundamental questions about the underlying neural mechanisms driving clinically significant changes in episodic memory.…”
Section: Introductionmentioning
confidence: 99%
“…PD is a common clinical neurodegenerative disease, patients may develop dyskinesia that interferes with normal activity, neurological abnormalities and cognitive impairment may occur when the condition is serious, it then causes the corresponding dysfunction, which affects the health and quality of life of the patients (Malak et al, 2017). Therefore, it is of great significance to treat PD timely and effectively and reduce the occurrence of cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%